Empathic expressions among three-year-olds in play and interaction in ECEC institutions in Norway: bodily empathic expressions purposed for peers' well-being and confirming relationships. Issue 9 (29th July 2019) - Nergaard, Kari
ABSTRACT: This article is based on video observations of three-year-old children's empathic expressions in the context of playful interactions in early childhood education and care (ECEC) institutions in Norway. The data were analysed within a hermeneutic phenomenological approach, searching for a system of the children's self-initiated empathic expressions in their play and interaction. The findings show that young children's inherent empathy largely appears as an embodied intonation in the other's emotional state, expressed through facial and bodily intersubjective expressions, followed up with empathy-related responses adapted to the context through physical communication. This study reveals that funny behaviour and play invitations are empathically motivated actions, making peers happy again and confirming relationships. This new insight contributes to a broader understanding of young children's empathy and may contribute to developing the knowledge of how ECEC's educational work can support children's empathic development based on an understanding of the body's phenomenology and integrated in children's play.